Exploring Asnaf Students’ Acceptance of an Islamic-Integrated English Module in Malaysian Muslim Orphanage - Zakaria, Nur Yasmin Khairani; Hashim, Harwati; Jamaludin, Khairul Azhar (UIN Salatiga, 2025)
English language proficiency, particularly communicative competence, is essential for socio-economic mobility. Communicative competence in English refers to the ability to communicate effectively in all contexts. However, asnaf students—underprivileged Muslim individuals from Islamic backgrounds—often encounter Western-centric content that can lead to feelings of alienation and eventually limits their learning. Recognizing this need, the present study explores the integration of Islamic content into a communicative English module to create a more inclusive and responsive educational experience for asnaf students. Utilizing a Design and Development Research (DDR) model, this study comprises three phases: analyzing students’ learning needs, developing content for the module, and evaluating asnaf students’ acceptance of the module. Data were collected through semi-structured interviews and classroom observations, where researchers recorded students’ engagement in class and participants reflected on their learning experiences. Thematic analysis revealed four key themes: confidence in spoken English, connection to Islamic-integrated content, participation in tasks, and challenges in the English language. The study noted several limitations, including a small sample size and a relatively short intervention period, impacting generalizability. Future research could replicate the module in different socio-religious settings or employ quantitative approaches to further assess its effectiveness on language performance.